Study on the microscopic damage evolution and dynamic fracture properties of sandstone under freeze-thaw cycles - Niu, Caoyuan; Zhu, Zheming; Zhou, Lei; Li, Xiaohan; Ying, Peng; Dong, Yuqing; Deng, Shuai (Cold regions science and technology, 2021)
Freeze-thaw has great deterioration effect on rock mechanical performance, which strongly affect the stability of rock masses engineering. Meanwhile, natural fractures in real rocks are ubiquitous with considerable variations in size, number, and orientation, which further accelerate the risk of geological disasters. In this study, the microstructure changes of specimens induced by cyclic freeze-thaw were measured using nuclear magnetic resonance (NMR) technique. Dynamic fracture tests were performed using single cleavage triangle (SCT) red sandstone specimens. Crack propagation gauges (CPGs) were applied to determine the crack velocity. Meanwhile, the microstructure of the fracture surface was obtained with the aid of scanning electron microscope (SEM). The results show that the cyclic freeze-thaw plays an important part in rock dynamic fracture behavior. The porosity and crack velocity increase with freeze-thaw cycles, whereas the crack initiation time and dynamic fracture toughness decrease with freeze-thaw cycles. Sandstone has three pore types and is susceptible to the freeze-thaw weathering. The fracture surface of specimen without freeze-thaw is smooth and the fracture mode is transgranular. With the rise of freeze-thaw cycles, the fracture surface becomes rougher, indicating that intergranular fracture plays a dominant role in sandstone failure. •Impact tests were conducted using large-size single cleavage triangle specimen to study the fracture process of rock.•The crack initiation time and crack propagation velocity of red sandstone subjected to freeze-thaw cycles were detected.•NMR technique was used to study the microscopic damage evolution of sandstone subjected to freeze-thaw cycles.